Cross-sectional analysis of the associations between age and body weight at first calving and productivity in spring-calving Holstein-Friesian dairy cows - H. Costigan; D.P. Berry; S. Walsh; E. Kennedy (Animal, 2025)
Age at first calving (AFC) is one of the key determinants of heifer rearing costs. Although a young AFC is recommended in order to minimise the non-productive period, calving at a young age has previously been associated with a reduction in milk production. Heavier BW at first calving may, however, negate the suboptimal performance associated with such a younger age at first calving. The objective of this study was to quantify the associations, using data collected on eight Irish research farms over a 15-year period, between both age and BW at first calving (as measured between 5 and 20 days postcalving) and performance thereafter in pasture-based seasonal-calving Holstein-Friesian dairy cows. A total of 2 924 calving, lactation, reproductive performance, BW and body condition score (BCS) records from 1 323 parity one to three cows were available for analysis. An interaction between BW at first calving, AFC, and parity only existed for mean milk protein percentage in the first 60 days of lactation, while a 2-way interaction between BW at first calving and AFC was not associated with any of the other performance variables considered. Age at first calving was not associated with either calving performance or any of the BW and BCS traits investigated. Although AFC was not associated with subsequent milk yield, it was associated with reduced milk fat and protein percentage in the first lactation for the youngest and oldest first−calving heifers. Older heifers at first calving had a shorter calving to first service interval in subsequent parities. BW at first calving was not associated with calving performance. A heavier BW at first calving, assuming a constant AFC, was associated with greater milk yield, 60 and 305-day milk fat percentage, and 305-day milk protein percentage in each of the first three lactations. Heavier heifers at first calving required fewer services to conceive, and had longer intervals from calving to first service, although there was no long-term influence of BW at first calving on reproductive efficiency. Heavier heifers at first calving were also heavier and more conditioned throughout the first, second, and third parities. Results from the present study are nonetheless confined to the ranges in AFC and BW at first calving in the study population. Performance was best when heifers had a median AFC between 738 and 768 days and a BW at first calving between 516 and 550 kg.